Seasonal analysis of commonly prescribed antibiotics in Istanbul city - Ikizoglu, Bahar; Turkdogan, Fatma Ilter; Kanat, Gurdal; Aydiner, Coskun (SPRINGER, 2023)
Antibiotics are among the most common medicine groups since they are used to treat infectious diseases, as nutritional supplements in livestock breeding, and for preservation in the food industry. Turkey is among the highest antibiotic consumers in the world. In the present study, the most popular 14 antibiotics available in Turkey were monitored in one hospital sewage and two urban wastewater treatment plant influents and effluents seasonally in Istanbul province, the largest metropolitan center in Turkey. The present research aimed to develop a robust analytical method to determine 14 antibiotics, including six chemical groups, in environmental matrices which are considered significant antibiotic pollution sources, namely hospital sewage and urban wastewater. Solid-phase extraction (SPE) and UPLC-MS/MS analysis parameters included optimized column temperature, eluent, mobile phase, and flow rate. Three SPE cartridges were employed in recovery studies. The antibiotic recovery rates varied between 40 and 100%, and all analytes were identified within 3 min with UPLC-MS/MS under optimal conditions. It was determined that method detection limits (MDLs) varied between 0.07 and 2.72 mu g/L for the antibiotics. In all seasons, the highest beta-lactam group antibiotic concentrations were identified in hospital sewage. The season with the greatest variety of antibiotics in urban wastewater was spring. Clarithromycin and ciprofloxacin were the antibiotics determined at the highest concentration in the influent and effluent of the wastewater treatment plant in all seasons. This study showed that the most widely used beta-lactam group antibiotics were found in high amounts in hospital sewage wastewater but in low concentrations in the treatment plants, and hence, it is seen that the degradability of beta-lactam group antibiotics was high. The presence of clarithromycin, ciprofloxacin, lincomycin, levofloxacin, and trimethoprim antibiotics in hospital sewage in higher amounts and also in inlet and outlet of wastewater treatment plants proves that those are resistant antibiotics.
Keywords: Antibiotics; UPLC-MS; MS; Hospital sewage; Urban wastewater; WASTE-WATER TREATMENT; SOLID-PHASE EXTRACTION; TREATMENT PLANTS; AQUATIC ENVIRONMENT; SURFACE-WATER; LC-MS/MS; PHARMACEUTICALS; REMOVAL; FATE; TRIMETHOPRIM; Environmental Sciences & Ecology